1994
DOI: 10.1002/kin.550260804
|View full text |Cite
|
Sign up to set email alerts
|

Rates of processes initiated by pulsed laser production of F atoms in the presence of HCl, CH4, and CF3H

Abstract: Time-resolved vibrational chemiluminescence from HF has been recorded following the production of F atoms by the pulsed laser photolysis (A = 266 nm) of F2 in the presence of HCI, CHI, and CF3H. In the first two cases, experiments have been conducted by observing emission from HF(v = 3) at four temperatures from 295 to 139 K. Rate constants have been determined over this range of temperature for the reactions of F atoms with HC1 and CH4 and of CH3 radicals with F2, and for the relaxation of HF(v = 3) by HC1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 35 publications
3
36
2
Order By: Relevance
“…The title reaction has been the subject of many theoretical [1][2][3][4][5][6][7][8][9] and experimental [10][11][12] studies. Experimentalists, have focused on the determination of thermal rate constants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The title reaction has been the subject of many theoretical [1][2][3][4][5][6][7][8][9] and experimental [10][11][12] studies. Experimentalists, have focused on the determination of thermal rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentalists, have focused on the determination of thermal rate constants. Wurzberg et al 10,11 and Moore et al 12 measured absolute rate constants in the temperature range 195-373 K and 195-294 K, respectively, using laser photolysis techniques. The measured thermal rate constants were found to follow a non-Arrhenius behavior over the studied temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…6 shows comparison of our calculated rate constant with the experimental results [19] and with the dynamics calculation by Corchado and EspinosaGarcia on the MJ1 PES [2,3] , using TST-CDSCSAG method and ICVT-CDSCAG method, separately. Wagner et al [4,15,19,25,42] reported the Arrhenius expression 4 F+CH k =5.5×10 −10 exp(−579/T)cm 3 /(molecule −1 s −1 ) for the temperature range of 253-352 K [4,25] . Moore, Smith and Stewart [19] reported recently a rather unusual temperature dependence.…”
Section: Resultsmentioning
confidence: 94%
“…Wagner et al [4,15,19,25,42] reported the Arrhenius expression 4 F+CH k =5.5×10 −10 exp(−579/T)cm 3 /(molecule −1 s −1 ) for the temperature range of 253-352 K [4,25] . Moore, Smith and Stewart [19] reported recently a rather unusual temperature dependence. Our results exhibit a linear dependence over the whole temperature range.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation